Depression in migrant workers and nationals of Qatar: An exploratory cross-cultural study - Salma M Khaled (6742259) (2019)
Background The aim of this study was to compare the prevalence of depressive symptoms among migrants and non-migrants living in Qatar and identify variables associated with depressive symptomology in these groups, including culture of origin, time living in country and perceived quality of life. In addition, we tested if the latter two variables moderated the effect of culture of origin on depressive symptomology in the migrant groups. Subject and Methods A telephone survey of a probability-based sample of 2,520 participants was conducted in February 2016. The sample was divided into three groups based on nationality and income: labour migrants (LMs), white-collar migrants (WCMs) and non-migrants or Qatari nationals (QNs). Participants completed the Whooley two-question test for depression. Results The odds of depression were significantly increased in LMs (OR = 3.31, 95% CI = 2.36–4.65) and WCMs (OR = 1.40, 95% CI = 1.04–1.90) compared with non-migrants. Among LMs, having a problem with current employer in the last 3 months was also associated with depressive symptoms (OR = 2.10, 95% CI = 1.14–3.84). Culture of origin was significantly associated with depressive symptoms including South Asians (OR = 3.12, p < .001), East Asians (OR = 0.52, p = .013) and Westerners (OR = 0.45, p = .044) relative to Arabs. LM status remained strongly associated with depressive symptoms independent of culture of origin (OR = 2.02, p < .001). Conclusion Perceived quality of life, but not length of stay, appears to be an important variable in explaining differences in symptoms between some cultural groups. Findings from this study highlight the importance of the context of migration and culture of origin as potential determinants of depressive symptomology in the host country. Other Information Published in: International Journal of Social Psychiatry License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/0020764019850589